Persepsi Mahasiswa Terhadap Penggunaan Google Translate Sebagai Media Menerjemahkan Materi Berbahasa Inggris - Maulida, Hidya (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2017)
The use of smartphone for helping students in studying is so familiar. It is used almost in every students’ studying activity. For example, it is often used for browsing material needed or for translating english word to indonesian or the opposite. In efforting to comprehend english material, students always try to translate it first. Google translate is a service often used by students to translate. This study describes of students’ perception towards the use of google translate to translate english material. Interview is used in collecting data. The subject is the seventh grade students by considering that based on prelimanary study, they use google translate and they get many assigments to translate English material. Data shows that students’ perception toward the use online dictionary in translating english material is positive. It is stated that google translate giving help a lot. Students can translate faster and complete their assignments. Although there is still weakness of translation result using google translate, google translate saves time in translating english material. The weakness of it overcome by rereading and fixing the translation with context. It is suggested to the students take other benefits of google translate.